عدالتی خلع اورپاکستانی عدالتوں کے فیصلوں کی روشنی میں اس کی قانونی بنیادیں: Judicial Khul’ and its Legal Grounds in the light of Decisions of Pakistani Courts - Muhammad, Aas; Habib, Prof. Dr. Rao Imran (Al-Amīr Research Journal for Islamic Studies, 2022)
The doctrine of Khul’ has, within the course of last few years, assumed a great deal of importance in Pakistan because literacy rate in women is increasing rapidly and their dependency on men is decreasing. Now, women can easily make their own decisions with free consent due to their some awareness about their rights, especially regarding dissolution of marriage. Majority of women is still ignorant about dissolution of marriage on the ground of Khul’. Therefore, it is very necessary to explain all different aspects of “doctrine of Khul’” for ensuring justice in our society. The present research has mainly explored the grounds of judicial Khul’ and other relevant incidents in the light of Pakistani Case Law based on Islamic family Law. The research is based primarily on the decisions of superior courts of Pakistan. The decisions of family courts of Pakistan have been included in the discussion. The relevant provisions of the Dissolution of Muslim Marriages Act, 1939 and the Family Courts Act, 1964 have also been debated. The difference between Khul’ and other modes of dissolution of marriage have also been elaborated briefly.